2023
DOI: 10.1021/acsaem.2c03260
|View full text |Cite
|
Sign up to set email alerts
|

Managing the Double-Edged Sword of Ni3+ in Sputter-Deposited NiOx by Interfacial Redox Reactions for Efficient Perovskite Solar Cells

Abstract: Nickel oxide (NiO x ) is widely used as a promising hole transport material for perovskite solar cells (PSCs). A high concentration of Ni 3+ in the NiO x film is generally beneficial for charge transport of the PSCs; however, chemical redox reactions between surface Ni 3+ and perovskite materials result in decomposition of perovskite materials, which causes carrier recombination and impedes charge transport at the perovskite−NiO x interface. Herein, we employ magnetron sputtering to fabricate NiO x thin films … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 49 publications
(86 reference statements)
0
20
0
Order By: Relevance
“…Then, sp-SnO 2 and Ag electrodes were deposited sequentially on top of the sputtering buffer layer using magnetron sputtering (Figure 1a). Based on a previous work, 29 the device energy band structure is shown in Figure 1b. This all-inorganic-CTL device has a matched energy band structure, which is conducive for building a built-in electric field and charge extraction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, sp-SnO 2 and Ag electrodes were deposited sequentially on top of the sputtering buffer layer using magnetron sputtering (Figure 1a). Based on a previous work, 29 the device energy band structure is shown in Figure 1b. This all-inorganic-CTL device has a matched energy band structure, which is conducive for building a built-in electric field and charge extraction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…are ionized and accelerated in an electric field, and then the high-energy Ar + exchanges momentum with the target surface atoms so that the target atoms have enough kinetic energy to break away from the target and deposit on the substrate. , Compared to other vapor deposition techniques, magnetron sputtering has the advantages of a fast deposition speed, dense and adhesive film formation, and relatively low requirements for equipment vacuum degree, making it a relatively robust deposition technique. , At the same time, due to its working principle of momentum exchange, the material selection of magnetron sputtering is wide and it can be applied to the deposition of most metals and oxide ceramics. It is worth noting that all functional layers in PSCs can be deposited by magnetron sputtering. Replacing the organic CTL with a sputtered inorganic CTL can also reduce cost and improve stability. However, the principle of magnetron sputtering determines that both the magnetron sputtering deposition of perovskite layers and the subsequent deposition of other films on perovskite layers will damage the soft lattice perovskite materials.…”
Section: Introductionmentioning
confidence: 99%
“…47,48,12,49 Peng et al demonstrated that a passivation of the NiO x surface is required to decrease Ni 3+ concentration at the NiO x /perovskite interface and avoid redox reaction between I − from the perovskite and Ni 3+ from the NiO x . 50 The main advantage of employing NiO x as HTM lies in the film uniformity and high yield of working devices (i.e., not shunted) when scaling the fabrication to larger cells (>1 cm 2 ) and modules compared to organic HTMs, which are typically only a few nanometers thick and thus more prone to pinholes. Prior to device fabrication, the RF-sputtered NiO x layer was annealed in air at 300 °C for 15 min.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Boyd et al showed that a redox reaction occurs at the interface between NiO x and perovskites, with the formation of an A-site deficient lead bromide/iodide phase at the surface, which accelerates interfacial recombination, thus reducing the V OC of the cells. Several studies attribute the limited V OC that is achievable with NiO x to nonradiative recombination at the perovskite interface with the HTM. ,,, Peng et al demonstrated that a passivation of the NiO x surface is required to decrease Ni 3+ concentration at the NiO x /perovskite interface and avoid redox reaction between I – from the perovskite and Ni 3+ from the NiO x …”
Section: Introductionmentioning
confidence: 99%
“…Different from the solution method, which is mainstream in the laboratory, magnetron sputtering is one of the most mature film deposition techniques in industry , with many advantages such as a fast deposition speed, uniform and dense film formation, solvent-free deposition process, and low vacuum degree requirements for the equipment. All functional layers of PSCs can be deposited by magnetron sputtering. , All these advantages make magnetron sputtering an attractive option for future industrial production.…”
Section: Introductionmentioning
confidence: 99%